2014
DOI: 10.1111/ppl.12282
|View full text |Cite
|
Sign up to set email alerts
|

Study on salt tolerance with YHem1 transgenic canola (Brassica napus)

Abstract: 5-Aminolevulinic acid (5-ALA) has been suggested for improving plant salt tolerance via exogenous application. In this study, we used a transgenic canola (Brassica napus), which contained a constituted gene YHem1 and biosynthesized more 5-ALA, to study salt stress responses. In a long-term pot experiment, the transgenic plants produced higher yield under 200 mmol L(-1) NaCl treatment than the wild type (WT). In a short-term experiment, the YHem1 transformation accelerated endogenous 5-ALA metabolism, leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 78 publications
2
18
0
Order By: Relevance
“…Then, the beneficial effect was confirmed in many other species, such as spinach (Nishihara et al ), pak choi (Wang et al ), potato (Zhang et al ), date palm (Youssef and Awad ), sunflower (Akram et al ), Swiss chard (Liu et al ), creeping bentgrass (Yang et al ), watermelon (Chen et al ), strawberry (Wu et al ), Brassica napus L. (Xiong et al ) and asparagus (Al‐Ghamdi and Elansary ). In transgenic plants, excessive biosynthesis of endogenous ALA can also improve salt tolerance in Arabidopsis (Zhang et al ), tomato (Li et al ) and canola (Sun et al ). Thus, the hypothesis that ALA improves salt tolerance in plants is supported by physiological and genetic evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the beneficial effect was confirmed in many other species, such as spinach (Nishihara et al ), pak choi (Wang et al ), potato (Zhang et al ), date palm (Youssef and Awad ), sunflower (Akram et al ), Swiss chard (Liu et al ), creeping bentgrass (Yang et al ), watermelon (Chen et al ), strawberry (Wu et al ), Brassica napus L. (Xiong et al ) and asparagus (Al‐Ghamdi and Elansary ). In transgenic plants, excessive biosynthesis of endogenous ALA can also improve salt tolerance in Arabidopsis (Zhang et al ), tomato (Li et al ) and canola (Sun et al ). Thus, the hypothesis that ALA improves salt tolerance in plants is supported by physiological and genetic evidence.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has been supported by many reports (Akram and Ashraf , Yang et al ). However, in transgenic tomatoes (Li et al ) and canola (Sun et al ), which over‐produce endogenous ALA, strong salt tolerance is always associated with higher H 2 O 2 . Miller et al () reported that Arabidopsis mutants lacking the cytosolic and/or chloroplastic H 2 O 2 ‐removal enzyme ascorbate peroxidase, were more salt tolerant.…”
Section: Discussionmentioning
confidence: 99%
“…According to these results, transgenic plants are able to survive under the salinity level in which wild-type plants are more sensitive ( Shafeinie et al., 2014 ). Given that 5-Aminolevulinic acid (5-ALA) exogenous application resulted in salt tolerance in treated plants, Sun et al. (2015) transformed canola with 5-ALA-encoding gene, YHem1, and studied the growth of the transgenic canola capable to synthesize more 5-ALA, and wild-type canola under salinity stress.…”
Section: Canola Molecular Salt-tolerance Mechanismsmentioning
confidence: 99%
“…6B). In a transgenic canola (Brassica napus) which can over-produce endogenous ALA, the leaf Clcontent is strictly limited to a very low level, even seedlings were stressed by 450 mM NaCl [51]. Additionally, in the previous study when the ion levels of xylem sap was measured, it was also found that ALA signi cantly depressed [Cl -] xylem under salt stress, which were 2.39, 6.20 and 3.50 μmol L -1 in the control, NaCl stress and NaCl + ALA, respectively.…”
Section: Discussionmentioning
confidence: 99%